2022
DOI: 10.5812/asjsm-129916
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Association of Shoulder Pain Risk with Physical Fitness in Badminton Players at National Tournament Level

Abstract: Background: Shoulder pain which affects sports performance and activities of daily life, is a common musculoskeletal problem experienced by badminton players. Objectives: This study aimed to identify the association of shoulder pain with physical fitness in elite university badminton players participating in the national tournament via medical check-ups. Methods: Physical fitness evaluations were performed among fifty-two 18 - 22 years old university badminton players participating in the national tournament. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Previous studies focusing on elite university badminton players aged 18–22 years revealed that badminton-related pain frequently localized in the shoulder (13.7%), lower back (13.2%), foot (11.7%), thigh (10.8%), knee (9.7%), elbow (9.2%), and ankle (9.0%) [ 14 ]. However, a past study on the overhead motion sports found different pain patterns among 6–15-year-old badminton players.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies focusing on elite university badminton players aged 18–22 years revealed that badminton-related pain frequently localized in the shoulder (13.7%), lower back (13.2%), foot (11.7%), thigh (10.8%), knee (9.7%), elbow (9.2%), and ankle (9.0%) [ 14 ]. However, a past study on the overhead motion sports found different pain patterns among 6–15-year-old badminton players.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent injury and ensure pain/injury-free badminton participation, a prevention approach should be implemented from the pre-adolescent stage. Previous studies have revealed that there are significant differences between extra hamstring muscle flexibility and badminton-related pain, as well as weak static balance ability and badminton-related pain [ 14 ]. Given the musculoskeletal and nervous system maturation levels of pre-adolescent and adolescent badminton players, it is essential to develop hamstring muscle flexibility and static balance ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracic spine rotation PROM <50 • : Either the dominant or non-dominant thoracic rotation PROM measured below 50 • when in a quadruped position [31,32] Total Body Rotation…”
mentioning
confidence: 99%